KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL FLIPPED CLASSROOM PADA PEMBELAJARAN KIMIA ABAD KE 21 - Shoimatul Maemanah; Siti Suryaningsih; Luki Yunita (Orbital: Jurnal Pendidikan Kimia, 2019)
The ability to solve problems is one of the ability to learn and innovate in the face of 21st century chemistry learning but the problem is that the ability to study chemistry is still low. Learning is still teacher-centered and there is a lack of student involvement, so one model is needed to improve it, the flipped classroom model. The purpose of this study was to determine the ability of problem solving through the flipped classroom model on the reaction rate material. The research method is descriptive quantitative in 34 students of MIPA 2 XI grade in one of the state high schools in Tangerang Regency. The instrument used was 16 essay test questions that were assessed using the problem solving scoring rubric according to Schoen and Oehmke on a scale of 1-10 then the scores were interpreted based on criteria according to Riduwan. The results of this study indicate that the ability to solve problems through the flipped classroom model has very good criteria with a percentage of 81.3. These results students are expected to compete and meet educational competence in the 21st century.